Religious Moderation and Classical Kalam Theory in Islamic Education: Tawassuth, Tawazun, and Iʿtidal from an Ashʿarite Perspective - Joni Harnedi; Awis Karni; Zaim Rais (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
Religious moderation has emerged as a strategic issue in Islamic education in response to the growing challenges of extremism, ideological polarization, and intolerance within pluralistic societies. Although the discourse on religious moderation has been widely examined from sociological, political, and educational policy perspectives, studies that critically connect it with the epistemological foundations of classical Islamic theology remain limited. This article analyzes the convergence between the principles of religious moderation—tawassuṭ (the middle path), tawāzun (balance), and iʿtidāl (justice)—and classical kalām theory, particularly within the Ashʿarite theological tradition, and explores their relevance for strengthening Islamic education. This study employs a qualitative library research design using a historical–philosophical and educational approach. Primary data are drawn from classical Ashʿarite theological texts, especially discussions on the synthesis of reason and revelation and the doctrine of kasb. In contrast, secondary data include scholarly books, peer-reviewed journal articles, and policy documents on religious moderation and Islamic education. Data analysis is conducted through thematic classification, critical-comparative reading, and conceptual synthesis. The findings indicate that religious moderation is not merely a contemporary policy agenda or a socio-political response to extremism, but a theological-educational paradigm deeply rooted in classical Islamic intellectual heritage. Ashʿarite theology, through its balanced integration of reason and revelation and its doctrine of kasb, provides a moderate framework that affirms both divine sovereignty and human moral responsibility. These findings imply that integrating classical kalām into Islamic education strengthens the epistemological legitimacy of religious moderation and supports the development of curricula and pedagogical models that are critical, inclusive, and contextually responsive to contemporary challenges.